(untitled) (Texas Journal of Engineering and Technology, 2023)
In this research, we will study the performance of the network and users in light of accessing the hybrid spectrum in the large (huge) cognitive radio network (CRN) so that we have primary users and secondary users when a primary user transmits on the same channel and at a uniform time (the same time) the user units are eclipsed Sub-state the channel through the sensing channel and draws the appropriate scheme for accessing the channel (it can be an overlay) for transmissions based on the results of the sensing channel. Controlled in order to produce less interference (the interference in the first network is less than the interference in the preceding), and when we don’t have primary users, the secondary user units do it = a transmission process under the overlay channel and thus increase the flow based on random geometry.